The network structure of posttraumatic stress symptoms in war‐affected children and adolescents - Florian Scharpf; Laura Saupe; Anselm Crombach; Roos Haer; Hawkar Ibrahim; Frank Neuner; Kirsi Peltonen; Samir Qouta; Regina Saile; Tobias Hecker (Wiley, 2023)
Abstract Background It is unclear whether findings from previous network analyses of posttraumatic stress disorder (PTSD) symptoms among children and adolescents are generalizable to youth living in war‐torn settings and whether there are differences in the structure and connectivity of symptoms between children and adolescents. This study examined the network structure of PTSD symptoms in a sample of war‐affected youth and compared the symptom networks of children and adolescents. Methods The overall sample comprised 2007 youth (6-18 years old) living in Burundi, Democratic Republic of Congo, Iraq, Palestine, Tanzania, and Uganda amid or close to war and armed conflict. Youth reported their PTSD symptoms using a self‐report questionnaire in Palestine and structured clinical interviews in all other countries. We computed the networks of the overall sample and of two sub‐samples of 412 children (6-12 years) and 473 adolescents (13-18 years) and compared the structure and global connectivity of symptoms among children and adolescents. Results In both the overall sample and the sub‐samples, re‐experiencing and avoidance symptoms were most strongly connected. The adolescents' network had a higher global connectivity of symptoms than the children's network. Hyperarousal symptoms and intrusions were more strongly connected among adolescents compared to children. Conclusion The findings lend support to a universal concept of PTSD among youth characterized by core deficits in fear processing and emotion regulation. However, different symptoms may be particularly important in different developmental stages, with avoidance and dissociative symptoms dominating in childhood and intrusions and hypervigilance gaining importance in adolescence. Stronger symptom connections may render adolescents more vulnerable to the persistence of symptoms.